Работы по ядерной спектроскопий выполненные с участием Монгольских Сотрудников в ЛЯП - Н, Ганбаатар; С, Даваа; Б, Далхсүрэн; Ж, Сэрээтэр (Scientific transaction of the National University of Mongolia. Physics, 2022)
Decay schemes of 150-157Er and 148-161Ho have been studied. β-, γ-, X-rays and conversion electrons were investigated and ten new isotopes and isomeric states were identified at the first time. Endpoint energies of β*-spectrum were measured using an intrinsic germanium detector, and Qec values have been obtained. A group of proton emitters of Au, Ir, Re and Ta have been identified, and the proton drip line was determined. Anisotropics of the gamma rays in well deformed Yb isotopes have been measured from the decay of radioactive Lu oriented at at low temperature. Multipole mixing ratio of the hundreds transitions have been deduced, about 170 of them uniquely and unambiguous spin assignments were made for 30 levels. External perturbations of two 171Yb levels have been observed. Study of the decay for 112-118In isotopes were the first nuclear physics experimental work in Mongolia. Mini-orange β*-spectrometer was constracted in Dubna for the inner conversion electrons measurements for neutron deficit nuclides. Measured conversion coclTicicnts were used for determination the transition mullipolaritics. A specific method for efficiency calibration of mini-orange spectrometer was applied using the continuous β* -spectrum of 90Sr in energy range from 500 to 2200 keV.